IDENTIFIKASI KAWASAN PERMUKIMAN KUMUH DI KAWASAN WURING, KABUPATEN SIKKA, NUSA TENGGARA TIMUR - Kristiana Bebhe; Yuliana Bhara Mberu (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2019)
Title: Identification of Slum Settlement in Wuring Area, Sikka District, East Nusa Tenggara The Wuring area, located in Sikka regency East Nusa Tenggara province. This settlement is dominated by the Bajo tribe and considered as a slum area. The identification of slum areas was carried out in order to provide basic data and slums-related information for local governments, planners, designers and area developers in making decisions or considerations in handling the slum settlement program. Determine criteria for slum areas was conducted by considering various aspects or dimensions such as the suitability of the location allotment related with spatial planning, land status (ownership), location, level of population and building density and physical, social, economic and cultural conditions of the local community. The study aims to identify and assess the location of slum areas in the Wuring area and furthermore recommend how the handling of this slum areas. For this purpose, the deductive research method using the criterias based on the Slum Settlement Identification Handbook issued by the Directorate of Settlement Development, Directorate General of Human Settlements, Indonesian Ministry of Public Works. The result of the study is that in the Wuring area has high level of slums and illegal land status.